Positive and Negative Species Interactions Shape Recruitment Patterns of a Range Expanding Native Alga - Voerman, Sofie E.; Gribben, Paul E.; Glasby, Tim M. (Frontiers in Marine Science, 2021)
A species’ ability to spread is in part governed by the extent to which recipient habitats either resist, tolerate or promote the species’ recruitment. In disturbed marine environments, there is a general trend for the loss of algal canopies, thought to resist invasion, towards algal turf or rock barrens habitat. This study tested whether the spread of the range-expanding native macroalga Caulerpa filiformis was resisted by algal canopies but facilitated by algal turf or barrens habitats. Large-scale field surveys generally supported the predicted recruitment patterns, with C. filiformis recruits being most abundant on turf (but not barrens) and absent under kelp canopies. However, a discrepancy existed between different structural forms of turf, with the positive association holding true only for geniculate corallines, not filamentous turf. Secondly, a laboratory experiment tested whether the physical structure and/ or the sediment-trapping properties of coralline turf influenced the recruitment success of C. filiformis. Whilst the structural complexity of turf aided overall recruitment performance (i.e. increased rhizoid production, attachment speed, success and strength), a positive influence of turf-derived sediment on recruits’ growth was less obvious, at least over 10 days. The high morphological plasticity of C. filiformis propagules resulted in possible benefits of faster or stronger attachment of more developed propagules being only temporary, and that recruitment may be regulated in accordance with habitat preference. Finally, a field experiment confirmed the observed positive role of turf and the negative influence of algal canopies in the short-term, however, adverse environmental conditions in the longer-term resulted in the loss of most fragments. In conclusion, this study demonstrated the importance of both positive and negative species interactions for the recruitment success of a native alga, suggesting that a shift from kelp to turf algae can initiate further community change.